Convenient synthesis of one-dimensional a-SEP@LDH via self-assembly towards simultaneously improved fire retardance, mechanical strength and thermal resistance for epoxy resin. (1st July 2021) - Zhang, Haijun; Hu, Xiaoping; Liu, Yingru; Zhang, Suhua; Wu, Zhenzhong
Abstract: It is essential to develop a class of EP composite with improved fire retardance, mechanical strength and thermal resistance performances for some practical applications, such as in aeronautic and automobile fields. Due to the highly tunable structure of layered double hydroxides (LDHs), transition metals Ni 2+ and Fe 3+ were selected as the cation components considering their excellent catalytic charring ability. To overcome the easy agglomeration of LDH during polymer process, sepiolite nanofiber (SEP) was used as a carrier for LDH and thus a novel low-cost one-dimensional flame retardant a-SEP@LDH was successfully synthesized via facile self-assembly. With the addition of 2.3 wt% a-SEP@LDH alone, EP composite owns a V-1 rating in UL-94 test, an LOI value of 31.1%, 21% reduction of peak heat release rate and decreased 16.0% total smoke production. Additionally, the total carbon monoxide production has been decreased by 25.3%. Combining the analyses of the char residue and thermogravimetric infrared spectrometry (TG-FTIR) of EP/a-SEP@LDH systems, the flame-retardant mechanism has been drawn as follows: a) physical solidified char residue by sepiolite nanofibers; b) reinforced char residue thanks to the catalytic charring effect of both Ni/Fe alloy catalyst (originated from partially reduced oxide metals) and Brønsted acid sites in sepiolite. Moreover, the tensile strength and glass transition temperature of EP composite have been enhanced simultaneously. In a nutshell, it is an economically effective channel targeting to improve the comprehensive properties of EP through loading Ni–Fe LDH assisted by sepiolite nanofibers. Graphical abstract: Image 1 Highlights: A novel one-dimensional multifunctional filler a-SEP@LDH composed of sepiolite and Ni–Fe LHD was successfully synthesized via low-cost self-assembly. Sepiolite fiber acts as an effective carrier to improve the dispersion of Ni–Fe LDH in EP matrix. EP/a-SEP@LDH composite exhibits enhanced fire retardance, mechanical strength and thermal resistance synchronously. The dual effect of LDH and sepiolite towards the high-quality char layer during combustion has been comprehensively investigated.